Análisis y simulación de transmisión de señales para emergencias usando el estándar ISDB-TMM de televisión digital terrestre en banda VHF en Quito - Enríquez Medina, Luis Alberto (2017)
In Ecuador, electromagnetic spectrum is a limited resource. Terrestrial Digital Television Transition Master Plan in Ecuador mentions that terrestrial digital television broadcasting (TDT) uses band UHF, and TDT transmission by using VHF band is available for ISDB-T norm advances. Moreover, Terrestrial Digital Television Broadcasting Service Technical Norm (RESOLUTION ARCOTEL-2015- 0301), it has information about UHF band frequencies and canalization. It has made the transmission station design, UHF band coverage simulation and VHF band coverage simulation through ICS TELECOM software. Channel Auxiliary transmission tests were done, it was verified 204 bits channel auxiliary distribution inside zero segment, that is part of the of the digital video transmission type 13 segments. It has identified the main natural disasters identified were earthquakes, landslides, and volcanic eruptions at Metropolitan District of Quito. The comparison between UHF band coverage and VHF band coverage, it shows that UHF band is the best with 19%. The comparison between ISDB-TMM standard and ISDB-TB standard, it shows that ISDB-TB standard is the best. UHF band design was chosen because of the economic viability when the VAN value is $7.404.36 and the TIR value is 17.65% to recover initial investment in one year.